Public sector pay in the UK - Jonathan Cribb; Carl Emmerson; Luke Sibieta (Institute for Fiscal Studies (IFS), 2014)
This report looks at trends in public sector pay and compares these with what has been happening in the private sector. We start by analysing the overall levels of public and private sector pay, including how they have evolved over recent years and the differences after accounting for the different composition of the public and private sector workforces. We then examine how the difference between pay in the public and private sector varies across different groups of workers and areas of the country. Finally, we consider the potenial consequences of differences in pay for the skills and abilities of workers in the public and private sector.
Keywords: 330